Pharmacogenomics of Anticancer Medicines: Mechanisms, Clinical Applications, and Future Perspectives - Devarajan S; Gayathri A; Dr.Shri Vijaya Kirubha T (Asian Journal of Pharmaceutical Research and Development, 2025)
Pharmacogenomics has become a vital tool in oncology, guiding the selection and dosing of anticancer medicines based on genetic makeup. Genetic variations in drug- metabolizing enzymes, transporters, and target genes play a pivotal role in determining therapeutic response and toxicity [1]. This review summarizes current understanding of pharmacogenomics in cancer treatment, highlighting key mechanisms, biomarkers, and clinical applications [2]. It also discusses challenges in implementing pharmacogenomics in routine practice, particularly in developing countries, and suggests future directions for integrating pharmacogenomics into personalized medicine strategies [3].